2017
DOI: 10.2494/photopolymer.30.533
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Transfer Performance for Antireflection Structured Films with Antifouling Properties via Partial-filling Technique

Abstract: Ultraviolet nanoimprint lithography (UV-NIL) is the most effective technique for mass fabrication of antireflection structure (ARS) films. For ARS films applied on touch-panel devices such as mobile phones and tablet computers, however, it is necessary to protect them from fingerprints and dust. Therefore, a UV-curable epoxy resin has been developed with antifouling properties for use with UV-NIL. However, because the developed epoxy resin possesses a high adhesive strength that ultimately reduces the lifetime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…One of a most popular methods for moth-eye fabrication is a combination of etching (dry or wet) and nanoimprint lithography (NIL). In the etching process, moth-eye-like structures are formed on a hard material, such as silicon [2], metal [3,4], carbon [7][8][9], or a ceramic [10]. In this process, masking is sometimes used to make regularly arranged patterns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of a most popular methods for moth-eye fabrication is a combination of etching (dry or wet) and nanoimprint lithography (NIL). In the etching process, moth-eye-like structures are formed on a hard material, such as silicon [2], metal [3,4], carbon [7][8][9], or a ceramic [10]. In this process, masking is sometimes used to make regularly arranged patterns.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ji et al reported a particle-masking method ('colloidal lithography') that uses a particle monolayer as a mask [11,12]. Processes that do not need masking have also been reported, whereby the moth-eye-like nanostructures are etched on glassy carbon using an oxygen ion beam [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…5,6) An anti-reflection structure called a moth-eye structure, simulating the eye of moth, can be created with a single layer and can be effective for a wide range of wavelengths and angles. [7][8][9] The moth-eye structure can be easily fabricated using ultraviolet nanoimprint lithography (UV-NIL), and if a highly durable mold is obtained, the productivity of the anti-reflection structure will be significantly increased. [10][11][12][13] However, the moth-eye structure has a lot of small and sharp needles with a height of several hundred nm to 1 μm and is easily broken during UV-NIL transfer.…”
Section: Introductionmentioning
confidence: 99%
“…However, this newly developed resin has a strong adhesive force. For this reason, ARS films have been produced by the partial filling method [8][9][10], which involves incompletely filling the resin. In the previous study, the antifouling properties and durability of ARS films produced from high-hardness UV curable resin were evaluated.…”
Section: Introductionmentioning
confidence: 99%